Association of Reduced Factor VIII with Impaired Platelet Reactivity to Adrenalin and Collagen after Total Thyroidectomy - Palareti, G; Biagi, G; Legnani, C; Bianchi, D; Serra, D; Savini, R; Coccheri, S (Thrombosis and Haemostasis, 1989)
Twenty-one thyroprival patients, previously submitted to total thyroidectomy for tumours, were investigated during stabilized L-thyroxine supplementation and at the end of a 20-25 day “no-therapy” period, necessary for a 131I total body scintigraphy. During supplementation therapy a lower than normal mean betathromboglobulin (beta-TG) release level was found, the other blood clotting and platelet function tests being normal. After substitution therapy withdrawal, platelet function tests showed reduced adrenalin aggregation, increased collagen threshold aggregating concentrations, decreased beta-TG release values and reduced aggregation to ristocetin, whereas blood clotting tests showed prolonged aPTT values and reduced levels of factor VIII: C and vWf: Ag. We conclude that in acquired hypothyroidism the lowering of factor VIII: C and vWf: Ag (acquired von Wille brand disease) is associated with impaired platelet reactivity not only to ristocetin but also to collagen and especially adrenalin. In the patients investigated these changes were almost completely corrected by substitutive therapy with L-thyroxine at clinically effective doses.
Keywords: Acquired hypothyroidism; L-thyroxine treatment; Factor VIII; Platelet function; Adrenalin aggregation